Looking through the Opera Glasses: Performance and Artifice in "The Age of Innocence." - Skaggs, Carmen Trammell (Mosaic: An Interdisciplinary Critical Journal, 2004)
Serving as a structural frame for Edith Wharton's novel "The Age of Innocence," opera illustrates the duality of the artifice of performance: the one on the stage and the one in the opera box. The artifice of opera allows its participants to express their imagination and passion; however, the artifice of the conventional behavior of the elite stifles its conformists. In the historical context of Newland Archer's New York, opera marks the opening of the winter season, delineates the inner circle of privilege, and exemplifies the wealth and leisure of this class. In the novel, unbridled passion and fulfillment are not allowed to triumph, even on the opera stage. The dual performances, the one on the stage and the one in the opera box, converge, and artifice triumphs.